Relationship Between Peer Relationships and Mental Health Among High School Adolescents - Juliyanti, Juliyanti (Open Access Health Scientific Journal, 2025)
Background: Adolescence is a developmental period filled with challenges, including physical, emotional, and social changes. Peer interactions significantly influence adolescent mental health. Positive peer relationships provide emotional support, boost self-confidence, and help adolescents develop healthy social skills. Conversely, negative relationships or lack of social interaction can increase the risk of mental disorders such as anxiety, stress, and depression. This study aimed to analyze relationship between peer relationships and mental health among high school adolescents.Methods: This study employs a quantitative method with a cross-sectional design. The sample consists of 246 adolescents from five high schools in Bandung, selected using a proportionate stratified random sampling technique. Mental health assessment was conducted using the Strengths and Difficulties Questionnaire (SDQ), while peer relationships were evaluated based on social indicators. Data analysis was performed using the chi-square test to examine the relationship between variables.Results: Bivariate analysis revealed a significant relationship between peer relationships and adolescent mental health (p = 0.000). About 50.8% of respondents had good peer relationships, while 49.2% did not. In terms of mental health, 51.6% of respondents were categorized as normal, 21.5% as borderline, and 26.8% experienced mental health disorders.Conclusion: Peer relationships have a significant impact on adolescent mental health. Support from schools, parents, and healthcare professionals is essential in creating a healthy social environment and preventing mental health issues among adolescents.